PSVIII-22 Effect of nitro-treatment on ruminal metabolism of poultry litter nonprotein nitrogen. (7th December 2018) - Copado-Garcia, R; Hume, M; Moreno-Degollado, G; Anderson, R; Estrada-Gandarilla, M; Nisbet, D; Arzola, C; Ruiz-Barrera, O; Castillo-Castillo, Y; Ontiveros-Magadan, M; Corral-Luna, A; Salinas-Chavira, J
Abstract: Poultry litter (PL) is a valuable nitrogen feed source for ruminants whose gut microbes transform the nitrogen in uric acid into microbial protein. Evidence indicates that nitro-treatment may improve the feed value of composted PL by inhibiting degradation of its nonprotein nitrogen (NPN) during composting but it is not known what effect residual nitrocompounds may have on ruminal NPN metabolism. In this study, freshly collected ruminal fluid from a pasture-reared cow was incubated anaerobically (10 mL/tube) at 39oC in closed-culture tubes supplemented with 0.2 g ground alfalfa, 0.15 g of one-year-old PL and with or without 20 mM 3-nitropropionate (NPA) or ethyl nitroacetate (ENA), concentrations previously shown to be inhibitory of uric acid degradation. Analysis of uric acid, urea and ammonia concentrations measured at 0, 6 and 24 h revealed rates of uric acid and urea disappearance in nitro-treated cultures did not differ from controls (0.10, 0.07 and 0.19 µmol urea 0.09, 0.05 and 0.07 µmol uric acid per mL incubation fluid for controls, NPA- and ENA-treated cultures, respectively). Rates of ammonia accumulations in NPA-treated cultures were similar to controls but lower in ENA-treated cultures (0.16, 0.17 and 0.09 µmol/mL, respectively). Effects of nitro-treatment were observed on headspace gas accumulations, although this was not unexpected as the nitrocompounds are known methane-inhibitors. Less gas volume accumulated in NPA- and ENA-treated cultures compared to controls (26, 21 and 18 mL, respectively) and methane production was lower in NPA- and ENA-treated cultures than controls (0.7, 0.5 and 21 µmol/mL, respectively). Hydrogen accumulations were similar between NPA-treated cultures and controls but higher in ENA-treated cultures (0.1, 0.4 and 0.9 µmol/mL, respectively). These results indicate that residual nitrocompounds in nitro-treated PL will have little if any adverse effect on ruminal NPN metabolism and may beneficially contribute to lowering methane emissions.